Exploring the Potential of Local Cuisine as a Cultural Tourism Attraction in Sawahlunto City: Traditional Culinary Products and Sustainable Destination Competitiveness - Azilla Retlika Andani; Lise Asnur (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to identify and analyze the potential of local cuisine as a cultural tourism attraction in Sawahlunto City, West Sumatra. A qualitative approach with a case study design was employed to obtain an in-depth understanding of the contribution of traditional culinary products to tourism development. Data were collected through field observations, in-depth interviews, and documentation involving tourists, culinary business owners, local communities, and representatives from the Sawahlunto Tourism Office. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data reduction, data display, and conclusion drawing. The findings revealed that four traditional culinary products, namely Kerupuk Kubang, Lamang Tungkek, Dendeng Batokok, and Ale-ale Apam, possess distinctive ingredients, traditional preparation methods, and cultural values that enhance their attractiveness as tourism assets. These culinary products enrich visitors' experiences, strengthen the cultural identity of Sawahlunto, and contribute to destination competitiveness. However, their tourism potential has not been fully optimized due to limited promotion and stakeholder collaboration. Strengthening partnerships among government institutions, local communities, and culinary entrepreneurs, supported by digital marketing strategies, is essential for promoting sustainable culinary tourism while preserving local cultural heritage.